(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
The economic activity of human society is the main factor contributing to the development of the modern landscape. In order to preserve the high ecological quality of the human environment, protect nature and effectively use natural resources, it is necessary to comprehensively take into account and consider any (direct and indirect) man-made changes in the natural environment. That is why today the study of ecogeomorphogenesis in a changing climate and anthropogenic impact is more urgent than ever and the primary task for the preservation of the environment in a supportive state. In this regard, the purpose of this work was to consider the situation of ecogeomorphogenesis in the territory of the Nura River basin, i.e. to show the current state of assessment and accounting of anthropogenic impact for the disclosure of ecogeomorphogenesis of the river basin. The article considers the types of modern processes in the Nura River basin. The data on cartographic and textual material on the geology and morphology of the Nura River basin for the modern period of time were used as the research material, geographical and comparative methods were used. In this paper, the main characteristics and the current state of ecogeomorphogenesis of the Nura River basin are investigated. Based on the results of the study, engineering-geological complexes of rocks were identified based on a set of geological and genetic features, including porphyry-tuff-porphyry, limestone, conglomerate-sandstone-mudstone, mudstone- sandstone-siltstone-coal, clay-gypsum, loam-clay, sandy loam-loam, loam-clay-sand-gravel, mudstone- sand-gypsum and sand and gravel complexes. The current state of ecogeomorphogenesis of the Nura River basin suggests that the rocks have some modifications and deformations as a result of anthropo- genic impact and climate change, with the representation of such formations as effusive, carbonate in the group of rocks, upper terrigenous in the composition of semi-rock. Of the modern geological processes, physical weathering is widely developed. Weathered marls from the surface to the state of heavy loams (up to a depth of 0.5-6 m) have the following physical and mechanical characteristics: natural humidity 16.4-26.1%, porosity coefficient 0.48-0.82, water saturation coefficient 0.82-0.95, total moisture capacity 24.8-29.2, calculated resistance 3.5-4 kg/cm2. Key words: ecogeomorphogenesis, river basin, geology, geomorphology, geological and lithological features.